2003
DOI: 10.1037/0735-7044.117.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Activation of serotonergic neurotransmission during the performance of aggressive behavior in rats.

Abstract: High aggression is often linked to lowered serotonin (5-HT) neurotransmission. Although this may hold for high aggression as a trait characteristic of an individual, serotonergic activity is probably increased during performance of aggressive behavior. To test this hypothesis, first, the 5-HT1A agonist alnespirone and gamma aminobutyric acid-A agonist muscimol were administered into the dorsal raphe nucleus. These treatments, which inhibit 5-HT neuronal activity, were shown to decrease performance of aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…In contrast, a positive correlation was found between the level of trait-like aggression (high or low) and levels of 5-HT and 5-HIAA in rats (44). Besides, a number of studies have reported that 5-HT release is stimulated by aggressive social interaction in lizards (45)(46)(47) and is increased during performance of aggressive behaviors in rats (13), suggesting that the enhanced 5-HT release is an important event for promoting and sustaining aggressive behavior. In line with this hypothesis, in recent reports 5-HT 1A and 5-HT 1B agonists, which reduce extracellular concentration of 5-HT through their inhibitory actions at somatodendritic and terminal autoreceptors (48,49), decreased offensive aggressive behavior in rats (50,51).…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, a positive correlation was found between the level of trait-like aggression (high or low) and levels of 5-HT and 5-HIAA in rats (44). Besides, a number of studies have reported that 5-HT release is stimulated by aggressive social interaction in lizards (45)(46)(47) and is increased during performance of aggressive behaviors in rats (13), suggesting that the enhanced 5-HT release is an important event for promoting and sustaining aggressive behavior. In line with this hypothesis, in recent reports 5-HT 1A and 5-HT 1B agonists, which reduce extracellular concentration of 5-HT through their inhibitory actions at somatodendritic and terminal autoreceptors (48,49), decreased offensive aggressive behavior in rats (50,51).…”
Section: Discussionmentioning
confidence: 70%
“…Secondly, while the changes in the 5-HT system during the aggressive act itself was not addressed in this review, it has to be mentioned that a display of defensive aggressive behavior is positively related to brief spikes of 5-HT neuronal activity. (84) Finally, although these results indicate the important role of the genes encoding pivotal proteins in 5-HT neurotransmission in modulation of aggressive behavior, the 5-HT system is certain to work in concert with other neurotransmitter genes. There is no doubt that a firing 5-HTergic neuron is connected with numerous other cells and receives impulses from different neurotransmitters.…”
Section: Discussionmentioning
confidence: 89%
“…Accumulated evidence has suggested an inverse relationship between serotonin level in cerebrospinal fluid (CSF) and brain with impulsivity, or escalated aggression, and suicide (Lee and Coccaro, 2001;van Praag, 1998). In rodents, some studies have shown a similar relationship with decreased serotonin and 5-HIAA levels associated with increased offensive aggression (Chiavegatto et al, 2001;Chiavegatto and Nelson, 2003;Ferrari et al, 2005;van der Vegt et al, 2003).…”
Section: Neurochemical Differencesmentioning
confidence: 95%